2009
DOI: 10.2340/16501977-0323
|View full text |Cite
|
Sign up to set email alerts
|

Disability assessment interview: The role of detailed information on functioning in addition to medical history-taking

Abstract: Information on participation and activity limitations provided by the patient has only limited influence on inter-rater reliability. However, there was a significant difference in scores on assessed work limitation items compared with medical history-taking alone. Therefore, in disability assessment interviews physicians should ask for medical information as well as detailed information on participation and activity limitations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 16 publications
1
31
0
Order By: Relevance
“…Self-classification and classification on the basis of disease codes results in the same classification for 75% of the respondents in the physical, mental and mixed groups, for 66% of the respondents in the mental and mixed groups, for 90% in the physical and mixed groups, and for 96% in the physical and mental groups. It would thus seem that the perceived limitations indicated by the client to a large extent predict the outcome of the examination conducted by insurance physicians and occupational health physicians as is indicated in other studies [1, 2, 4, 5]. Self-classification has been chosen as the main validation criterion, while the questionnaire may also be useful as an inventory of the limitations perceived by the client who submits an application to the insurance or occupational health physician.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Self-classification and classification on the basis of disease codes results in the same classification for 75% of the respondents in the physical, mental and mixed groups, for 66% of the respondents in the mental and mixed groups, for 90% in the physical and mixed groups, and for 96% in the physical and mental groups. It would thus seem that the perceived limitations indicated by the client to a large extent predict the outcome of the examination conducted by insurance physicians and occupational health physicians as is indicated in other studies [1, 2, 4, 5]. Self-classification has been chosen as the main validation criterion, while the questionnaire may also be useful as an inventory of the limitations perceived by the client who submits an application to the insurance or occupational health physician.…”
Section: Discussionmentioning
confidence: 92%
“…To map the abilities and limitations of the client, insurance and occupational health physicians make use of an insurance-medical research consisting, among other things, of an assessment interview [1–3]. Several studies have noted that the assessment to a large extent is based on the information reported by the insured persons themselves [1, 4, 5]. In a qualitative study, 94 insurance physicians were interviewed about the sources of information they used to assess clients’ work limitations [2].…”
Section: Introductionmentioning
confidence: 99%
“…The latter was also applied in our study. In an earlier study, Spanjer et al [18] reported a comparable inter-rater agreement of IPs on the items on physical abilities of the LFA in simulated assessments of claimants with low back pain or a lower extremity disorder, based on written interview reports of assessments in practice. Before that, similar results were found in a study of Spanjer [19] into the predecessor of the LFA, the work capacity profile of the Function Information System (FIS).…”
Section: Discussionmentioning
confidence: 98%
“…Previous research by Spanjer et al [9] has shown that the more information about the client the IP has, the higher the number of work limitations the IP will find. A study by Schellart et al [10] of inter-doctor variation between assessments by IPs found that greater adherence to the rules by IPs leads to a greater number of clients being assessed as the highest category of work disability.…”
Section: Introductionmentioning
confidence: 99%